Identification of phenol in urine in workers with professional exposure - Raičević, Ema; Milovanović, Nada; Mihajlović, Filip; Đorđević, Snežana (Medicinski časopis, 2023)
Introduction: Due to the increasing use of phenol in various industries, the Central Serbiaregion has an increased need for toxicological analyses. Toxicological measurements areimplemented as a preventive measure to avoid occupational diseases, which is the primary goalof all occupational medicine institutions. Objective: To demonstrate the significance of continuous biological monitoring of workersexposed to benzene, phenol, and phenolic resins, as well as the rapid and easy detection ofphenol in urine by a semi-quantitative method. Materials and methods: The study was designed as an analytical, observational, retrospectivecross-sectional study. It was based on a toxicological analysis of phenol concentration inworkers’ urine and the processing of documented results from the records of regular systematiccheck-ups at the ZZZR Zastava facility between January 2018 and December 2022. Results: The values of phenol in the urine of 61 patients were processed through statistical dataanalysis of patient records, of which 58 were male (95%), and three were female (5%). Astatistically significant difference in phenol concentration in urine was shown when consideringage (0.03<0.05) and male patients (0.02<0.05). Furthermore, the study did not reveal astatistically significant correlation between age and measured concentrations of phenol inworkers’ urine (0.07>0.05). Conclusion: Biological monitoring of workers exposed to phenol and its derivatives is importantfrom the perspective of professional toxicology. Exposure time, individual patientcharacteristics, and age are some of the factors that need to be taken into account wheninterpreting and issuing results. Semi-quantitative method for determining phenolconcentration in urine has been shown to be fast, easy, and reliable. Due to the increasing needfor phenol analysis, it is necessary to perform one of the more modern chromatographic methodsfor final confirmation of concentration. Keywords: phenol, benzene, bisphenol A, professional toxicology, petrochemical and militaryindustry, biomonitoring of workers